Improving Students’ Writing Skills Through The Use of Punctuation in Writing Descriptive Texts at SMP Negeri 3 Beo - Pangke, Alcelcius; Maru, Mister G.; Liando, Nihta V. F (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2024)
The purpose of this study is to ascertain whether using punctuation correctlysuch as hyphens (-), parentheses (), commas (,), and periods (.) can help students write better descriptive texts. Using a pre-test and post-test design and quantitative methods, the study was carried out with eighth-grade students at SMP Negeri 3 Beo. A multiple-choice test with ten questions was used to gather data. A pre-test was given to the students before they were taught how to use punctuation. They completed a post-test to gauge their progress following the treatment.The pre-test results revealed a standard deviation of 7.54 and an average score of 57.82. The post-test results, on the other hand, showed a notable improvement, with an average score of 85.22 and a standard deviation of 6.30. These results imply that mastering proper punctuation significantly improved students' descriptive writing abilities.According to the study's findings, teaching punctuation improves students' writing skills and motivates teachers to incorporate activities that emphasize punctuation into their writing classes. This study emphasizes how crucial it is to use focused language teaching techniques to raise students' general writing proficiency.